Preparation, Characterization and Evaluation of Starch Phosphate as a New Disintegrant in Tablet Formulations - Chowdary, K.P.R.; Enturi, Veeraiah; Bhagya Lakshmi, K. (Asian Journal of Chemistry, 2011)
Starch phosphate prepared by reacting potato starch with di-sodium hydrogen orthophosphate anhydrous at elevated temperatures was found to be a white, crystalline, non-hygroscopic powder. Starch phosphate prepared exhibited excellent flow characteristics. Starch phosphate is insoluble in water and aqueous fluids of acidic and alkaline pHs. It also exhibited good swelling (400 %) in water. It has no pasting or gelling property when heated at 100 ºC in water for 0.5 h. As starch phosphate exhibited good swelling in water it is considered as a promising disintegrant in tablet formulations and was evaluated as disintegrant in tablet formulations. Tablets of (i) piroxicam (20 mg) and (ii) paracetamol (120 mg) were prepared by wet granulation method employing starch phosphate at 5 and 10 % strength as disintegrant and were evaluated. For comparison tablets were also prepared employing crospovidone (a super disintegrant) as disintegrant at 5 and 10 % strength in the tablets. Piroxicam and paracetamol tablets formulated employing starch phosphate (both wet and dry addition) disintegrated within 1-3 min. Wet addition of starch phosphate gave relatively fast disintegration than dry addition with both the drugs. Piroxicam and paracetamol tablets formulated employing starch phosphate as disintegrant gave rapid and higher dissolution of the contained drug when compared to those formulated with crospovidone and commercial product in each case. Wet addition of starch phosphate gave relatively faster dissolution with both the drugs than dry addition. Thus starch phosphate, a new modified starch, is found to be a promising disintegrant in tablet formulations and can be used in a concentration of 5-10 % as an efficient disintegrant.